Efficacy of transverse cerebellar diameter/abdominal circumference ratio: a gestational age independent parameter in assessing fetal growth restriction - Chinnappan, Saritha; Loganathan, Malarvizhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: It is important to identify fetal growth restriction (FGR) antenatally because it is associated with increased perinatal morbidity and mortality. There is difficulty in diagnosis of fetal growth restriction using standard ultrasonographic parameters as they are gestational age related and are not reliable in cases of symmetrical growth restriction. Therefore, there is a need for gestational age independent biometric parameter, which can diagnose fetal growth restriction in unknown gestational age and can diagnose both symmetric and asymmetric fetal growth restriction. In this study transverse cerebellar diameter (TCD)/abdominal circumference (AC) ratio used to diagnose fetal growth restriction. Objectives of the study were to evaluate the validity of TCD/AC ratio in diagnosing fetal growth restriction and to find out the cut-off value of TCD/AC ratio for diagnosis of fetal growth restriction. Methods: This study was carried out for 12 months and sample size was 100. Transverse cerebellar diameter, abdominal circumference measured between 20-22wks and 32-34weeks of gestation and transverse cerebellar diameter and abdominal circumference ratio calculated. Results: TCD/AC ratio was fairly constant throughout the pregnancy. Fetuses with TCD/AC ratio more than 2SD of the mean were found growth restricted on examination. The TCD/AC ratio more accurate in diagnosing fetal growth restriction (FGR). Conclusions: As the TCD/AC ratio is constant, it is a gestational age - independent parameter, can diagnose FGR in antenatal women with unknown gestational age. Hence, TCD/AC ratio can be a screening test to diagnose FGR in the antenatal period.